Transport in laser microfabrication : fundamentals and applications - Grigoropoulos, Costas P. (Cambridge University Press, 2009)
Emphasising the fundamentals of transport phenomena, this book provides researchers and practitioners with the technical background they need to understand laser-induced microfabrication and materials processing at small scales. It clarifies the laser/materials coupling mechanisms, and discusses the nanoscale confined laser interactions that constitute powerful tools for top-down nanomanufacturing. In addition to discussing key and emerging applications to modern technology, with particular respect to electronics, advanced topics such as the use of lasers for nanoprocessing and nanomachining, the interaction with polymer materials, nanoparticles and clusters, and the processing of thin films are also covered.